Evaluation of the Effect of Climate Change Factors, Sustainable Agricultural Practices, and Community Involvement on Sustainable Agricultural Productivity: A Case Study on Rice Farmers in Cianjur Area - Fatma Sarie; Wily Mohammad; Dewa Oka Suparwata; Fitriah Suryani Jamin (Westscience Press, 2023)
This research investigates the interplay of climate change factors, sustainable agricultural practices, and community involvement on agricultural productivity, focusing on rice farmers in the Cianjur area. Through a quantitative analysis involving 121 farmers, descriptive statistics, correlation, and multiple regression analyses were employed to unveil patterns and relationships. The results reveal a moderate positive correlation between climate change awareness and productivity, a strong positive association between sustainable practices and productivity, and a robust positive correlation between community involvement and productivity. Multiple regression analysis indicates that, collectively, these factors significantly contribute to agricultural productivity. The findings underscore the importance of holistic approaches that integrate climate resilience, sustainable practices, and community engagement for enhancing agricultural productivity in the Cianjur region.